2011
DOI: 10.1089/thy.2010.0267
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Analysis of the RET Proto-Oncogene Key Exons in Patients with Medullary Thyroid Carcinoma: A Comprehensive Study of the Iranian Population

Abstract: This is the first comprehensive genetic screening and analysis of MTC among Iranian families. The results further confirm the need and advantages of DNA sequencing for identification of hereditary MTC cases. There does not seem to be a meaningful correlation between single nucleotide polymorphism patterns and the average age of disease onset. Geographical distribution of the sporadic cases, however, shows a significant concentration toward the Northern regions of the country, noticeably the provinces situated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
24
2
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(28 citation statements)
references
References 38 publications
1
24
2
1
Order By: Relevance
“…Results presented by M. Hedayati et al in the current issue, in addition to those previously presented by Alvandi et al [18], are illustrative of the mutational profile observed among Iranian patients with MTC.…”
supporting
confidence: 78%
“…Results presented by M. Hedayati et al in the current issue, in addition to those previously presented by Alvandi et al [18], are illustrative of the mutational profile observed among Iranian patients with MTC.…”
supporting
confidence: 78%
“…the Czech Republic they represent 21.7% (23/106) of MTC patients (20,25). The relevant percentage in Spain is 22.8% (26/114) (22).…”
Section: European Journal Of Endocrinologymentioning
confidence: 95%
“…Interestingly, a very high incidence of C634G germline mutation (5 cases out of 43) was observed in Iranian patients with hereditary MTC, indicating that the observed C634G might represent a founder effect [22]. However, another study also of Iranian patients with hereditary MTC published in the same year did not report any C634G mutations, which may be related to the different genetic background of the patients involved in the study [21].…”
Section: Test (Units)mentioning
confidence: 89%
“…Postoperative Levels of Plasma Fractionated Free Metanephrines few cases with C634G mutations described in Germany [13,14], the Netherlands [13,15], Italy [16,17], Romania [18], India [19] and Iran [20,21], but mainly among patients with hereditary MTC or MEN2A without pheochromocytoma. Interestingly, a very high incidence of C634G germline mutation (5 cases out of 43) was observed in Iranian patients with hereditary MTC, indicating that the observed C634G might represent a founder effect [22].…”
Section: Test (Units)mentioning
confidence: 99%